Formation of the Subject of Study of Economic Problems of the North of Russia (to the 300th Anniversary of the Russian Academy of Sciences) - Lazhentsev, V. N. (Studies on Russian economic development, 2022)
— The article demonstrates the experience in forming the topics of academic research on the economic problems of the North of Russia. Those scientific areas that reflect the most significant trends in the development of the northern and Arctic regions have been identified. The subject of assessing the impact of extreme and difficult natural conditions on life support and economic activity has been updated. The growing role of studying the mobilization economy is emphasized. Some scientific and organizational activities in terms of North Arctic research are noted.